A Sweet Tale = Aik Meethi Kahani - Rumana Husain; Illustrated by Priya Kuriyan (Karachi Oxford University Press, 2014)
Sonia and Anya are very fond of sweets and so are their parents and grandparents. Find out what happens when there are too many sugary delights to tempt this sweet-loving family.
Include Illustrations.
Keywords: Short English Stories -- Short Urdu Subtitles Stories -- Short Stories -- Pakistan Oxford Books